ANALYSIS OF THE ECONOMIC IMPACT OF E-COMMERCE IN EMERGING MARKETS - Prasad H K (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Procrastination in the healing process of modernisation is a term better used with solving health issues when referring to lost time, investments, human resources diminished, and the resulting in inefficiency. The past five years to have witnessed considerable e-commerce economic impact on emerging economies; this study with recent review provides GDP contribution, employment generation, digital infrastructure impact, cross-border trade etc. The e-commerce platforms have not only provided local businesses with access to larger markets but also to investments from abroad enabled by the improved capabilities in mobile technology, logistics and payment gateways. The research is through secondary data analysis which investigates trends and patterns between 2019 and 2023 in certain emerging economies including India, Brazil, Indonesia, and South Africa. This study also employs inferential statistical instruments to determine if the observed economic changes were statistically significant, and correlates those changes with e-commerce growth indicators. An overview of the existing literature reveals that despite the positive impact of e-commerce on inclusive growth, challenges like digital divide, regulatory barriers and cybersecurity threats remain. These results confirm our expectation that e-commerce statistically significantly enhances economic states in developing economies.